Ratcheting of 316L stainless steel thin wire under tension-torsion loading - Sichao Fu; Dunji Yu; Gang Chen; Xu Chen (Fracture and Structural Integrity)
A series of cyclic tension-torsion tests under symmetric shear strain and asymmetric axial stress control in various loading paths are conducted on 100 μm-diameter 316L steel wires applying a micro tensiontorsion fatigue testing apparatus. The ratcheting strain of the thin wire increases with increasing axial mean stress and decreases in a sequence of linear, rhombic and circular paths. The macro-scale based cyclic plastic constitutive models with kinematic hardening rules of the Ohno-Wang (OW) and the Chen-Jiao-Kim (C-J-K) are evaluated for the thin wire. Comparing with the O-W, the C-J-K predicts more accurately under high axial stress. While the loading path effects on ratcheting for wire specimens are basically simulated, the macro-based models tend to under-estimate the effect of phase difference between axial and torsional loadings and the ratcheting evolution in the initial 50 cycles